The Relationship Between Enterprise Financial Risk and R&D Investment Under the Influence of the COVID-19 - Li, Xinfei; Cheng, Baodong; Li, Yueming; Duan, Jingyang; Tian, Yuan (Frontiers in Public Health, 2022)
The COVID-19 pandemic has dealt a considerable blow to the development of Chinese enterprises. Therefore, exploring how to reduce the enterprise financial risk under the impact of the COVID-19 has become a current research hotspot. We select the data of 3,098 A-share companies in the quarters of 2019 and 2020, use the Z-score model to reasonably evaluate enterprise financial risk, and analyze the impact of Research and Development (R&D) investment on enterprise financial risk under the COVID-19.The results show that: ① The COVID-19 pandemic has increased the number of high-risk enterprises. ② R&D investment can effectively reduce the enterprise financial risk, and enterprises that attach importance to scientific research are relatively less affected by the COVID-19. ③ Compared with non-state-owned enterprises, R&D investment under state-owned enterprises can better help enterprises reduce financial risk. ④ When the enterprise financial risk is lower, the role of R&D investment in reducing financial risk is more significant. With the increase of financial risk, the effect of R&D investment on it is weakened. The research results are beneficial to help enterprises to correctly assess their financial risks during the COVID-19, so that enterprises can reasonably invest in research and development, and ultimately ensure the sustainable development of enterprises under the COVID-19.